The practicality of forensic auditing techniques to detect non-government orgnaisations’ financial statement fraud in South Africa using a proactive approach - Jean Damascene Mvunabandi; Bomi Cyril Nomlala; Harold Patrick (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
This article empirically investigated proactive financial statement fraud detection techniques 30 among nongovernment organisations in the eThekwini region, South Africa. The data for this thesis was gathered from 87 staff via the use of a mixed research method with knowledgeable individuals in the field of fraud risk management. SPSS used descriptive statistics analysis while all the interview questions were analysed using conventional thematic analysis via NVivo. Robustness analysis was entirely performed using AMOS for CFA was used to estimate statistical models. SEM simultaneously estimated the link between detective financial statement fraud practices. The study’s results and findings of both the questionnaire and interviews reflected statistically significant agreement that NGOs should use proactive forensic auditing techniques in order to detect financial statement fraud among NGOs in the eThekwini region of South Africa.